The Spatio-Temporal Evolution of China’s Hydrogen Fuel Cell Vehicle Innovation Network: Evidence From Patent Citation at Provincial Level - Yu, Pei; Jiang, Feng; Cai, Zhengfang; Sun, Yongping (Frontiers in Environmental Science, 2021)
Hydrogen fuel cell vehicle industry is in a rapid development stage. Studying the domestic spatial distribution of hydrogen fuel cell vehicle industry across a country, especially the spatio-temporal evolution of the innovation level and position of each region in innovation network, will help to understand the industry’s development trends and characteristics, and avoid repeated construction. This article uses social network analysis and patent citation information of 2,971 hydrogen fuel cell vehicle related invention patents, owned by 218 micro-innovators across 25 provinces of China from 2001 to 2020, to construct China’s hydrogen fuel cell vehicle innovation network. Based on the dimensions of knowledge production, knowledge consumption and network broker, the network positions of sample provinces in three periods divided by four main national policies are classified. The main findings are as follows. (1) In China, the total sales of hydrogen fuel cell vehicle and the development of supporting infrastructure are balanced, and a series of national and local industrial development polices have been issued. (2) China’s hydrogen fuel cell vehicle innovation network density, the proportion of universities and research institutes among the innovators, and the active degree of the eastern provinces are all becoming higher. (3) The provinces in optimal network position are all from the eastern region. Shanghai and Liaoning are gradually replaced by Beijing and Jiangsu. (4) Sichuan in the western region is the only network broker based on knowledge consumption. (5) Although Zhejiang, Tianjin, Hebei, Guangdong, and Hubei are not yet in the optimal position, they are outstanding knowledge producers. Specifically, Guangdong is likely to climb to the optimal network position in the next period. The conclusions will help China’s provinces to formulate relevant development policies to optimize industry layout and enhance collaborative innovation in hydrogen fuel cell vehicle industry.